PENGARUH PENAMBAHAN STARTER Lactobacillus Sp. TERHADAP NILAI pH DAN TOTAL ASAM LAKTAT SILASE RUMPUT Panicum maximum - Sri Sumarsih; Bambang Sulistiyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
The aim of the research was to evaluate the effect of Lactobacillus Sp. as starter on pH and total Lactic Acid of Panicum maximum Grass Silage. The completely randomized design was been used on this research with 4 treaments and 4 replications. The treatments were different level LAB (0,2,4 dan 6% v/w). The parameters were pH value and lactc acid. The results showed that pH value were significantly (p<0.05) decreased, and Lactic acid were significantly (p<0.05) with addded of Lactobacillus Sp. on Panicum maximum Grass Silage. The conclusion was the use of starter Lactobacillus Sp. on ensilage process produces chemical qualities of good Panicum maximum silage.